Antibacterial activity of copper nanoprticles and Watercress (Nasturtium officinale R. Br.) extracts (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study was aimed to detect the antibacterial activity of N. officinale leaves water and ethanol extract alone or mixed with a specific concentrations of copper nanoparticles (800mg/L). Studied Bacterial samples consist of two gram-positive bacteria (Escherichia coli and Pseudomonas aeruginosa) and two gram-negative bacteria (Staphylococcus aureus and Streptococcus pyogenes). Results showed that there was a significant increase in the mean inhibition zone at 1:1 (v/v) of  1.0mg/10ml copper nanoparticles and water leaves extract (J) and 1:1 (v/v) of  0.5mg/10ml mg/10ml  copper nanoparticles and ethanol leaves extract (F)  compared with 0.5mg/10ml leaves water extract (B) and 0.5mg/10ml leaves ethanol extract (C), but there was no significant differences obtained between the types of treatments and the standard antibiotic that used as control (250 mg/10ml Cefotaxime), the highest mean inhibition zone was recorded in Staphylococcus aureus bacteria compared with other bacterial species. The interaction revealed that the highest mean inhibition zone obtained in 1:1 (v/v) of  1.0mg/10ml copper nanoparticles and water leaves extract (J) in Staphylococcus aureus bacteria and the lowest mean inhibition zone observed in 1.0mg/10ml copper nanoparticles (I) in Pseudomonas aeruginosa bacteria while mean inhibition zone significantly increased in E. coli bacteria at 1:1 (v/v) of  0.5mg/10ml mg/10ml  copper nanoparticles and ethanol leaves extract (F), 1:1 (v/v) of  1.0mg/10ml copper nanoparticles and water leaves extract (J), and 1:1 (v/v) of  1.0mg/10ml copper nanoparticles and ethanol leaves extract (K). No significant differences recorded in the mean inhibition zone of Pseudomonas aeruginosa and Staphylococcus aureus bacteria in various treatments.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 564-571